Neuropathogenesis of severe acute respiratory syndrome coronavirus 2. Issue 6 (22nd December 2021) - Patel, Payal B.; Bearden, David
Abstract : Purpose of review: The purpose of this review is to address our current understanding of the pathophysiology of neurologic injury resulting from severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection on the developing nervous system. Recent findings: SARS-CoV2 may enter the brain through three potential mechanisms: transsynaptic spread from the olfactory bulb following intranasal exposure, migration across the blood–brain barrier through endothelial cell infection, and migration following disruption of the blood–brain barrier from resulting inflammation. SARS-CoV2 does not appear to directly infect neurons but rather may produce an inflammatory cascade that results in neuronal injury. Additionally, autoantibodies targeting neuronal tissue resulting from the immune response to SARS-CoV2 are present in select patients and may contribute to central nervous system (CNS) injury. Summary: These findings suggest that neuronal injury during SARS-CoV2 infection is immune mediated rather than through direct viral invasion. Further multimodal studies evaluating the pathophysiology of neurologic conditions in pediatric patients specifically following SARS-CoV2 infection are needed to improve our understanding of mechanisms driving neurologic injury and to identify potential treatment options.